COMPARATIVE STUDY OF CORROSION INHIBITORS FOR REBAR STEELS IN SIMULATED PORE SOLUTION CONTAINING SEAWATER AND CARBONATES - Arini Nikitasari; Faty Alvina; Efendi Mabruri (Pusbindiklat - LIPI, 2016)
The performances of sodium nitrite and dimethylethanolamine (DMEA) inhibitors have been compared in mitigating corrosion of rebar steels in simulated pore solution containing sea water and carbonates. The simulated solution was prepared by dissolving saturation amounts of alkali hydroxides and sulphates in sea water and adding carbonates subsequently. The inhibitor of sodium nitrite and DMEA with various concentration was then added to the respective simulated solution. The corrugated rebar steels were immersed in the solutions and electrochemical corrosion was measured using potentiodynamic polarization method. The experimental results showed that sodium nitrite exhibited more effective performance compared to DMEA in mitigating rebar steel corrosion in sea water and carbonated media. The lowest steel corrosion rate of 0.27 M Sodium nitrite with 0.3 M concentration decreased corrosion rate of the steel to 0.27 M, the lowest values of the measured corrosion rates this work.